The adoption of research data management practices by emerging researchers: A case study of emerging researchers at a higher education institution in the Western Cape, South Africa - Xesi, Xabiso (Library and Information Studies Centre (LISC), 2025)
Research Data Management serves a crucial role in navigating the intricate landscape of contemporary research. This study, comprising five chapters, adopts a qualitative approach and leverages Activity Theory to explore the factors that influence researchers' Research Data Management practices and comprehend how practices relate to the Research Data Management environment at the institution. The research design uses semi-structured interviews to collect data from Masters and Doctoral students (referred to as ‘emerging researchers' in the study) and librarians as representatives of Research Data Management stakeholders within the institution. Document analysis was employed as a complementary tool to acquire insight into the current situation of Research Data Management in the institution under investigation. The collected data was analysed using thematic analysis. The study findings provide insight into a wide range of Research Data Management practices, including various storage options, issues with metadata documentation, complex opinions on data preservation and sharing, and a solid dedication to ethical considerations. These practices were influenced by factors such as Research Data Management practices and continual education and communication initiatives to teach a better awareness of the benefits throughout the research lifecycle. The study offers several recommendations, including prioritising research training programs, establishing transparent communication channels for institutional Research Data Management policies, fostering collaborative platforms, and providing ongoing support and education. Finally, this study provides foundational insights into the complex interaction of factors that influence Research Data Management practices, laying the groundwork for creating effective methods to build a culture of responsible data management within academic institutions.